Knowledge and beliefs of endocrine disruptors in pediatrics: all hands on deck! - Portefaix, Aurélie; Loppinet, Thomas; Tourvieilhe, Laura; Balice, Giuseppe; de Veron de La Combe, Nathan; Kassai, Behrouz; Bacchetta, Justine (Frontiers in Public Health, 2024)
Endocrine disruptors (ED) are ubiquitous pollutants, possibly implicated in chronic disease. Exposure of vulnerable populations; including neonates, infants and children; must therefore be limited. Informing parents is now a public health challenge. We conducted a quantitative cross-sectional study at the Lyon Mother and child Hospital. We used questionnaires to assess the beliefs and knowledge about ED of parents and pediatric healthcare professionals in the pediatric ward in Lyon, France. A total of 746 questionnaires were completed: 444 for professionals and 302 for parents. The majority of both populations had already heard of ED but only 10% of parents and 5% of professionals felt sufficiently informed. Professionals answered better than parents (73% vs. 60%). The main source of information was similar: media. Only 20% of professionals had read a scientific article about ED and 4% have followed a training. Environmental exposure and EDs is an increasing concern for parents but specific knowledge remains scare for parents and professionals. Specific training is needed.